The 46, XX Ovotesticular Disorder of Sex Development With Xq27.1q27.2 Duplication Involving the SOX3 Gene: A Rare Case Report and Literature Review - Zhuang, Jianlong; Chen, Chunnuan; Li, Jia; Jiang, Yuying; Wang, Junyu; Wang, Yuanbai; Zeng, Shuhong; Lin, Yiming; Xie, Yingjun (Frontiers in Pediatrics, 2021)
Background: Very few reports are available on human XX ovotesticular disorder of sex development involving SOX3 gene duplication. Here, we aim to present a rare case of SOX3 gene duplication in Chinese population who exhibit XX ovotesticular disorder of sex development. Case presentation: A 7-year-old Chinese individual from Fujian province Southeast China was recruited who exhibited 46,XX karyotype, absence of sex-determining region Y and was diagnosed with XX ovotesticular disorder of sex development. Further SNP array detection results demonstrated that the patient had a 2.2-Mb duplication in the Xq27.1q27.2 region (arr[hg19]Xq27.1q27.2:139,499,778-141,777,782) involving SOX3 genes. Additionally, no SOX3 duplication was observed in the parents and the sibling who showed normal phenotype. Conclusion: We identified the first case of SOX3 duplication exhibited ovotesticular disorder of sex development in Chinese individual. Our study strengthens the link between the SOX3 duplication and XX ovotesticular disorder of sex development and indicated that SOX3 is the evolutionary antecedent of sex-determining region Y.